If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(x/2)/3 = 6 // - 6
(x/2)/3-6 = 0
1/6*x-6 = 0 // + 6
1/6*x = 6 // : 1/6
x = 6/1/6
x = 36
x = 36
| 6x^3/3x+12 | | 11-k/8=6 | | 3x+8=23-3x | | 6x+4+x=2+2-18 | | -75x=0 | | X+2-2(x-4)=0 | | x/-7=8.1 | | 7g(3g+5x)= | | x^2+y^2-18x+10y+70=0 | | y^2=-6 | | 1.07x=44.94 | | 3x^2+10x-12=-4 | | x^2-8x=6 | | 1/(x^2)=14 | | 6x^3+9x^2+-5x+2=0 | | 8/9x-1=4/5x | | (-1/400)*x^2+1100 | | 3(3r+4)=-33 | | 6x^3+9x^2-5x+2=0 | | 5x+7y=7 | | x+12=5x-2 | | 15x+2y=2 | | x-2*(77-x)-8=0 | | x^2+12x+11x=0 | | 6x^3+9x^2-5x=-2 | | -(4y+3)-(-3y-6)=-4 | | 1100-x/400 | | (3*x-162)/(77-x)=0 | | 30=-16t^2+50t+6 | | 12x-5-2x=25 | | 1100-x/400(x) | | (x-8)/(77-x)=2 |